2017
DOI: 10.1001/jamasurg.2017.1032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery Program Implementation in 2 Surgical Populations in an Integrated Health Care Delivery System

Abstract: IMPORTANCE Novel approaches to perioperative surgical care focus on optimizing nutrition, mobility, and pain management to minimize adverse events after surgical procedures. OBJECTIVE To evaluate the outcomes of an enhanced recovery after surgery (ERAS) program among 2 target populations: patients undergoing elective colorectal resection and patients undergoing emergency hip fracture repair. DESIGN, SETTING, AND PARTICIPANTS A pre-post difference-in-differences study before and after ERAS implementation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 28 publications
5
110
1
6
Order By: Relevance
“…A study has demonstrated that prolonged fasting diminished the gastrointestinal peristalsis and caused irregular contraction waves instead of frequent eating peristalsis and regular contraction waves [31]. Therefore, postoperative early oral feeding not only accelerates intestinal function recovery, but also provides nutrients needed during recovery to maintain the intestinal mucosal barrier function and further accelerate organ recovery [8,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has demonstrated that prolonged fasting diminished the gastrointestinal peristalsis and caused irregular contraction waves instead of frequent eating peristalsis and regular contraction waves [31]. Therefore, postoperative early oral feeding not only accelerates intestinal function recovery, but also provides nutrients needed during recovery to maintain the intestinal mucosal barrier function and further accelerate organ recovery [8,32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, adding whey protein in preoperative CHO loading could reduce further the postoperative insulin resistance that otherwise leads to an increase in catabolism of skeletal muscle and results in body fat and protein loss [9]. Early oral feeding postoperatively provided early energy protein supply and subsequently reduced the risk of further catabolism due to a negative energy protein balance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization that likely contribute to shorter recovery without increased readmission and complications (Table 4). Other institutions have shown LOS in ERAS spine surgery was decreased by 1.5 to 2 days with no change in complication or readmission rate (15,16). So n (17) described an ERAS protocol for lumbar surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of 481 manuscripts screened, 37 individual ERPs were published in 37 studies including 41 centres as shown in Figure S1. There were 18 cohort studies, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] seven historically controlled studies, [33][34][35][36][37][38][39] five guidelines, [40][41][42][43][44] four randomized controlled trials (RCTs), [45][46][47][48] one RCT protocol, 49 one case series 50 and one narrative review. 51 Institutions in Europe were the most frequent study locations (25 of 37, 67.6%), followed by North America (10 of 37, 27%), Asia (4 of 37, 10.8%) and Oceania (2 of 37, 5.4%), respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%